Protection Law For Client Notary Public Who Experienced Losses Due To Forged Authentic Deeds - Ramadhani, Diva Arista Putri; Rodliyah; Suhartana, Wira Pria (Private Law, 2025)
This study seeks to determine and analyze the legal protection available for notary clients against the forgery of authentic deeds, as stipulated in Constitution Number 1 Year 2023 concerning the Criminal Code in Indonesia. Additionally, it aims to examine the legal responsibilities associated with the forgery of authentic deeds perpetrated by notaries. The research methodology employed is normative legal research. The findings indicate that the legal protection available for notary clients who incur losses due to forgery can be classified as repressive protection under civil law, which encompasses the provision of compensation, as well as under criminal law according to Law Number 1 Year 2023, specifically Article 391, Article 392, and Article 394. Furthermore, a notary may bear responsibility for the content of an authentic deed that he or she has executed if such action arises from negligence or intentional wrongdoing, thus implicating civil, criminal, and administrative accountability, in addition to the Notary’s Code of Ethics.